Quinoline: An Attractive Scaffold in Drug Design - Moor, Lucas F.E.; Vasconcelos, Thatyana R.A.; da R. Reis, Raisa; Pinto, Ligia S.S.; da Costa, Thamires M. (Mini Reviews in Medicinal Chemistry, 2021)
Quinoline and its derivatives comprise an important group of heterocyclic compounds that exhibits a wide range of pharmacological properties such as antibacterial, antiviral, anticancer, antiparasitic, anti-Alzheimer and anticholesterol. The quinoline nucleus is found in the structure of many drugs and rational design in medicinal chemistry for the discovery of novel bioactive molecules. Persistent efforts have been made over the years to develop novel congeners with superior biological activities and minimal potential for undesirable side effects. This review highlights some discoveries on the development of quinoline-based compounds in recent years (2013-2019), focusing on their biological activities, including anticancer, antitubercular, antimalarial, anti-ZIKV, anti-DENV, anti- Leishmania and anti-Alzheimer’s disease.
Keywords: biological activity